2023
DOI: 10.1038/s41467-023-40895-6
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated single-cell tumor microenvironment dynamics reinforce pancreatic cancer subtype

Ki Oh,
Yun Jae Yoo,
Luke A. Torre-Healy
et al.

Abstract: Bulk analyses of pancreatic ductal adenocarcinoma (PDAC) samples are complicated by the tumor microenvironment (TME), i.e. signals from fibroblasts, endocrine, exocrine, and immune cells. Despite this, we and others have established tumor and stroma subtypes with prognostic significance. However, understanding of underlying signals driving distinct immune and stromal landscapes is still incomplete. Here we integrate 92 single cell RNA-seq samples from seven independent studies to build a reproducible PDAC atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…Complementarily, we here show that JUNB/AP1 acts as a counterpart to promote a favorable CLA phenotypic identity in PDAC. Of note, JUNB/AP1-mediated transcriptional programs can also confer tumor-promoting functions in other cancer types [39][40][41] ; JUN/AP1 TFs are highly context dependent and may co-operate for target gene transcription [41][42][43] or oppose one another 44 Altogether, this string of insights provides a potential mechanistic foundation for several recent studies that showed a high degree of heterogeneity in the neoplastic and stromal immune compartments in human PDAC, including hybrid/intermediate/coexpressor CLA/BL subtype states that exist in naive and therapy-treated PDAC tumors [10][11][12][13][14][15][16]20,36,37 . We propose that extrinsic regional TNF-α plays an essential role in destabilizing CLA neoplastic cell identity by promoting BL cJUN/AP1-mediated transcriptional programs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Complementarily, we here show that JUNB/AP1 acts as a counterpart to promote a favorable CLA phenotypic identity in PDAC. Of note, JUNB/AP1-mediated transcriptional programs can also confer tumor-promoting functions in other cancer types [39][40][41] ; JUN/AP1 TFs are highly context dependent and may co-operate for target gene transcription [41][42][43] or oppose one another 44 Altogether, this string of insights provides a potential mechanistic foundation for several recent studies that showed a high degree of heterogeneity in the neoplastic and stromal immune compartments in human PDAC, including hybrid/intermediate/coexpressor CLA/BL subtype states that exist in naive and therapy-treated PDAC tumors [10][11][12][13][14][15][16]20,36,37 . We propose that extrinsic regional TNF-α plays an essential role in destabilizing CLA neoplastic cell identity by promoting BL cJUN/AP1-mediated transcriptional programs.…”
Section: Discussionmentioning
confidence: 94%
“…Here, we investigated the role of neoplastic AP1-mediated epigenetic and transcriptional programs in shaping the local inflammatory TiME, which in turn is critical for intratumoral subtype plasticity and PDAC aggressiveness [10][11][12][13][14][15]20,36,37 . We report that AP1 transcription factors (JUNB/AP1 vs. cJUN/AP1) hold a dichotomous role in maintaining both the plasticity and stability of CLA and BL neoplastic cells via intrinsic epigenetic and transcriptional regulation of lineage gene expression as well as extrinsic inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that high expression of mainly E2F1 is predictive of a poor clinical outcome in PDAC patients (38, 39), while our analysis of E2F gene expression in PDAC tissue showed that low E2F8 expression was associated with poor disesease specific patient survival. Interestingly, E2F8 expression is mainly detected in the immunogenic PDAC subtype (40) and correlates with all the signature genes of the classical subtype (24, 41) but not with the genes linked to the basal subtype. These observations suggest that the low E2F8 expressing group in our survival group may identify patients with basal PDAC which have a much shorter DSS rate, while patients with classical PDAC have moderate to high E2F8 expression.…”
Section: Discussionmentioning
confidence: 97%
“…Log2 expression data was extracted from Maurer et al [ 18 ], Oh et al [ 19 ] and Moffitt et al [ 5 ] with R2 Genomics ( https://hgserver1.amc.nl/cgi-bin/r2/main.cgi?open_page=login ) and exported into GraphPad Prism (v7.03).…”
Section: Methodsmentioning
confidence: 99%